The CORRELATION BETWEEN NEUTROPHIL LYMPHOCYTE RATIO WITH DEATH IN CORONAVIRUS DISEASE 2019 PATIENTS AT RSUD DR. H. ABDUL MOELOEK LAMPUNG PROVINCE - Tibar, Fifi Nurliza Aini; Kurniati, Intanri; Rahmawati, Selvi (CV. Jasa Sukses Abadi, 2024)
World Health Organization (WHO) declared Coronavirus Disease 2019 (COVID-19) a pandemic as of March 9, 2020. Data as of October 8, 2021 recorded a total positive case of COVID-19 in Lampung Province were 49,304 cases with 3,790 deaths. Disease progression in COVID-19 patients was determined based on the results of laboratory tests. Several studies reported that the value of Neutrophil Lymphocytes Ratio (NLR) was strongly associated with clinical worsening and even death in COVID-19 patients. This study was purposed to determine the relationship between NLR with death in COVID-19 patients. This study was an observational analytic study with a cross sectional design. The sample was medical record data taken from 44 COVID-19 patients who survived and 44 COVID-19 patients who died in March 2020 - September 2021 at Dr. RSUD. H. Abdul Moeloek Lampung Province. The sample was selected using purposive sampling technique. Statistical analysis was performed by univariate and bivariate analysis. The result of the bivariate analysis with chi quare test showed the p value was 0.000 (p<0.5), which indicated that there were a relationship between NLR with death in COVID-19 patients at RSUD Dr. H. Abdul Moeloek Lampung Province. There were a statistically significant relationship between NLR with death in COVID-19 patients at RSUD Dr. H. Abdul Moeloek Lampung Province.